NEEDS ANALYSIS AND EFFECTIVENESS EVALUATION OF ENGLISH LANGUAGE TEACHING MATERIALS: A SYSTEMATIC LITERATURE REVIEW - Daffa Nirwana Wahyudi; Farah Fadhilah (PT. Intelek Cendikiawan Nusantara, 2025)
This study investigates how English Language Teaching (ELT) materials can be improved through needs analysis and effectiveness evaluation. The study intends to ascertain the true needs of students, assess the appropriateness of current resources, and ascertain the consequences for curricular improvement. Six pertinent publications published between 2021 and 2025 were examined using a Systematic Literature Review that was bolstered by case-based data from needs analysis and material evaluation studies. The results demonstrate that many ELT resources are still out of step with students' actual academic and communicative needs, especially in ESP environments. Research continuously shows that materials created through systematic requirements analysis like contextualized tasks and multimodal resources tend to be more successful and improve learner engagement and skill development. Evidence also indicates that authentic, relevant, and well-targeted materials improve language learning outcomes more reliably than generic textbooks. These results carry important implications for curriculum development, emphasizing the need for curricula to be responsive to learner profiles, workplace expectations, and evolving educational demands. Integrating needs analysis and effectiveness evaluation into curriculum planning can ensure that ELT materials become more adaptive, context-appropriate, and aligned with contemporary language-learning goals